Unsupervised mobile app-based cognitive testing in a population-based study of older adults born 1944 - Öhman, Fredrik; Berron, David; Papp, Kathryn V.; Kern, Silke; Skoog, Johan; Hadarsson Bodin, Timothy; Zettergren, Anna; Skoog, Ingmar; Schöll, Michael (Frontiers in Digital Health, 2022)
Background Mobile app-based tools have the potential to yield rapid, cost-effective, and sensitive measures for detecting dementia-related cognitive impairment in clinical and research settings. At the same time, there is a substantial need to validate these tools in real-life settings. The primary aim of this study was thus to evaluate the feasibility, validity, and reliability of mobile app-based tasks for assessing cognitive function in a population-based sample of older adults. Method A total of 172 non-demented (Clinical Dementia Rating 0 and 0.5) older participants (aged 76–77) completed two mobile app-based memory tasks—the Mnemonic Discrimination Task for Objects and Scenes (MDT-OS) and the long-term (24 h) delayed Object-In-Room Recall Task (ORR-LDR). To determine the validity of the tasks for measuring relevant cognitive functions in this population, we assessed relationships with conventional cognitive tests. In addition, psychometric properties, including test-retest reliability, and the participants’ self-rated experience with mobile app-based cognitive tasks were assessed. Result MDT-OS and ORR-LDR were weakly-to-moderately correlated with the Preclinical Alzheimer's Cognitive Composite (PACC5) (r = 0.3–0.44, p < .001) and with several other measures of episodic memory, processing speed, and executive function. Test-retest reliability was poor–to-moderate for one single session but improved to moderate–to-good when using the average of two sessions. We observed no significant floor or ceiling effects nor effects of education or gender on task performance. Contextual factors such as distractions and screen size did not significantly affect task performance. Most participants deemed the tasks interesting, but many rated them as highly challenging. While several participants reported distractions during tasks, most could concentrate well. However, there were difficulties in completing delayed recall tasks on time in this unsupervised and remote setting. Conclusion Our study proves the feasibility of mobile app-based cognitive assessments in a community sample of older adults, demonstrating its validity in relation to conventional cognitive measures and its reliability for repeated measurements over time. To further strengthen study adherence, future studies should implement additional measures to improve task completion on time.